Structural and Functional Characterization of RecG Helicase under Dilute and Molecular Crowding Conditions. (8th August 2012) - Saxena, Sarika; Nagatoishi, Satoru; Miyoshi, Daisuke; Sugimoto, Naoki
Abstract : In an ATP-dependent reaction, the Escherichia coli RecG helicase unwinds DNA junctions in vitro . We present evidence of a unique protein conformational change in the RecG helicase from an α -helix to a β -strand upon an ATP binding under dilute conditions using circular dichroism (CD) spectroscopy. In contrast, under molecular crowding conditions, the α -helical conformation was stable even upon an ATP binding. These distinct conformational behaviors were observed to be independent of Na + and Mg 2+ . Interestingly, CD measurements demonstrated that the spectra of a frayed duplex decreased with increasing of the RecG concentration both under dilute and molecular crowding conditions in the presence of ATP, suggesting that RecG unwound the frayed duplex. Our findings raise the possibility that the α -helix and β -strand forms of RecG are a preactive and an active structure with the helicase activity, respectively.